Heavy Metal Contamination in Groundwater around Industrial Estate vs Residential Areas in Coimbatore, India - K. Mohankumar (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Water is the vital resource, necessary for all aspects of human and ecosystem survival and health. Depending on the quality, bore water may be used for human consumption, irrigation purposes and livestock watering. The quality of bore water can vary widely depending on the quality of ground water that is its source. Pollutants are being added to the ground water system through human and natural processes. Solid waste from industrial units is being dumped near the factories, which react with percolating rainwater and reaches the ground water. The percolating water picks up a large number of heavy metals and reaches the aquifer system and contaminates the ground water. The usage of the contaminated bore water causes the diseases. Mercury, Arsenic and Cadmium are used or released by many industries. Aim: This study was conducted to investigate the pollution of bore water in the industrial region (Kurichi Industrial Cluster) of Coimbatore, in the state of Tamilnadu, India. Materials and Methods: Four samples were taken from residential areas around Kurichi Industrial Cluster and analysed to find the concentrations of Mercury, Arsenic and Cadmium. Four more samples were taken from other residential regions far from the industrial estate and served as control. Samples were analysed using Atomic absorption spectrophotometry method. Results: We found that the ground water of the areas surrounding the industrial cluster does not contain significant amount of those metals. Instead, Heavy metal contamination of ground water were observed in some residential areas of coimbatore. Conclusion: The regulatory measures to contain and prevent ground water contamination by industries undertaken by Tamilnadu pollution control board may have lead to absence of heavy metal contamination in Kurichi Industrial cluster, Coimbatore, India.